Ethno-Specific Codes: Metaphor and Everyday Symbolization of Objectified Space in Anna Nerkagy’s Story “The White Moss” - D. E. Ertner; O. B. Ulyanova; S. B. Khabibullina (Научный диалог, 2022)
The features of decoding ethnospecific codes of metaphorization in the literature of the peoples of the North are considered on the material of A. Nerkagy’s story “The White Moss”. This article is intended to reveal certain “algorithms of speech behavior” embedded in the language, the principles of mythologization and metaphorical objectification of the real world, to reveal more deeply the structure of understanding a literary text. The relevance of the study is due to the need to search for new tools to identify ethnospecific cultural models that determine the vision of the world of representatives of a particular national community, structuring the field of expressiveness of a literary text. Attention is paid to the formation mechanisms of figurative meanings, when the dynamics of the narrative, which is not bright at first glance, is compensated by a careful detailing of the description of a northerner life, which is achieved through the actualization of the sacred elements of the symbolic picture of the world. So, for A. Nerkagy’s creativity, mythological codes of imagery become ethnospecific: bird, wolf, stone, fire, time, water, man. The personification of objects of nature and the perception of the world through the prism of one’s own body are traced. Each of the listed semantic elements is an element of metaphor, metonymy. The symbolic image is indivisible; it is based not just on an associative component, but on a ritual, a myth.